Case Report: Identification of a Heterozygous XPA c.553C>T Mutation Causing Neurological Impairment in a Case of Xeroderma Pigmentosum Complementation Group A - García-Carmona, Juan Antonio; Yousefzadeh, Matthew J.; Alarcón-Soldevilla, Fernando; Fages-Caravaca, Eva; Kieu, Tra L.; Witt, Mariah A.; López-Ávila, Ángel; Niedernhofer, Laura J.; Pérez-Vicente, José Antonio (Frontiers in Genetics, 2021)
We aimed to determine if an adolescent patient presenting with neurological impairment has Xeroderma pigmentosum (XP). For this purpose whole-exome sequencing was performed to assess mutations in XP genes. Dermal fibroblasts were established from a skin biopsy and XPA expression determined by immunoblotting. Nucleotide Excision Repair (NER) capacity was measured by detection of unscheduled DNA synthesis (UDS) in UVC-irradiated patient fibroblasts. Genetic analysis revealed two recessive mutations in XPA, one known c.682C>T, p.Arg228Ter, and the other c.553C>T, p.Gln185Ter, only 2 cases reported. XPA protein was virtually undetectable in lysates from patient-derived fibroblast. The patient had significantly lower UV-induced UDS (3.03± 1.95%, p<0.0001) compared to healthy controls (C5RO=100±12.2; C1UMN=118±5.87), indicating significant NER impairment. In conclusion, measurement of NER capacity is beneficial for the diagnosis of XP and in understanding the functional impact of novel mutations in XP genes. Our findings highlight the importance of neurologists considering XP in their differential diagnosis when evaluating patients with atypical neurodegeneration.